JOINT VENTURE AND STRATEGIC ALLIANCE - Abdul Azis; Asmara Dewi; Auzar; Ganar Septyadi; Riduan Sihite; Indrayani; Muammar Khaddafi (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
This study aims to analyze the effect of Capital Adequacy Ratio, Non Performing Financing, Financing To Deposit Ratio and Operating Expenses and Operating Income on profitability at PT. Sharia Aceh Bank. Where in this study profitability is seen from the return on assets (ROA). This study uses a quantitative method using the Autoregressive Distributed Lag (ARDL) approach. This study uses time series data or time series data where this research was conducted during the period 2012 to 2021. The results of this study indicate that the Capital Adequacy Ratio partially has no effect, Non Performing Financing partially has a positive and significant effect, Financing To Deposit Ratio partially has an effect negative and significant,